Moral contamination: Perceptions of good (but not bad) deeds depend on the ethical history of the actor - Protzko, John; Schooler, Jonathan W. (Frontiers in Psychology, 2023)
In the majority of moral decision-making research, we are asked to consider the action of someone we know little about—an anonymous actor. This is inconsistent with our everyday judgments of the actions of others. Here we test the novel prediction of whether actions are considered as comparably virtuous or malignant when performed by a good person, an immoral person, or the standard anonymous actor. Across four sets of experiments (nine studies in total), we show that the moral status of the actor contaminates peoples’ evaluations of the virtue of their actions. Even without ulterior motives, people do not judge good acts consistently across actors. We also discover a dose–response relationship where the more immoral the actor has been in the past—the less credit they are given for a good action in the present. This process does not occur for good people performing bad acts, however. Bad acts are bad regardless of who commits them. These results give new insights into the way people evaluate the behaviors of others.